A synergistic effect of physisorption and chemisorption: Multiple H2 molecules on the ScC6H6 complex. (29th May 2020) - Ma, Li-Juan; Rong, Yifei; Han, Ting
Abstract: Investigation of the H2 dissociation and H migration on the 3d transition metal modified carbon nanomaterials is very important for better understanding the hydrogen storage mechanism. Herein, the adsorption processes including H2 dissociation and H migration on ScC6 H6 complex are studied systematically. The optimal adsorption pathway indicates that five H2 molecules are continuously adsorbed on ScC6 H6 until six adjacent CH2 groups is reached. The corresponding hydrogen storage capacity is up to 7.50 wt %. The optimal adsorption pathway is ScC6 H6 → 1d → 1a → 2a → 3b → 3e → 3c → 3d → 3a → 4a → 5b → 5c → 5a (ScC6 H12 (H2 )–2H), and the whole reaction is exothermic by 6.19 kcal/mol and 1.89 kcal/mol using B3LYP and CCSD(T) functional, respectively. It indicates that the adsorption of multiple H2 molecules on the ScC6 H6 complex is a synergistic process of physisorption and chemisorption. Graphical abstract: The optimal adsorption pathway of five H2 on ScC6 H6 . Image 1 Highlights: ScC6 H6 adsorb five H2 by chemisorption and physisorption. The adsorption product is hydrogenation isomer 5a (ScC6 H12 (H2 )–2H). The whole reaction is exothermic by 1.89 kcal/mol using CCSD(T) functional.